The Utilization of Performance Measurement System within Internal Audit Process at the Supreme Audit Institution of the Republic of Indonesia - Rivaldy, Aldre (2020)
Purpose: The research explores the utilization of performance measurement system (PMS) within internal audit process and investigates the factors that shape how internal auditors use the PMS data/information, in the setting of a government audit office in a developing country. Design/methodology/approach: Qualitative approach, using questionnaire with close and open-ended questions, semi-structured interview, and review of document, was conducted with a sample of 21 participants who are all internal auditors. Findings: Results show that internal auditors benefit from the PMS data/information. There is a varying degree of utilization of PMS within internal audit process, with an inclination toward diagnostic utilization rather than interactive utilization. The PMS itself is embedded with belief/boundary system, which act as prerequisite to other controls. Three factors, namely institutional, performance, and compliance issues has shaped the pattern of PMS utilization. Institutional factors are dominant and few internal forces such as politics and culture might demotivate innovation. Implications: Managerial implications include the need for the application of guidelines to be aligned and more frequent utilization of PMS interactively. Originality/value: This research contributes to the understanding of PMS utilization as a tool for control within internal audit process and the motivating factors. Keywords: performance measurement system, levers of control, diagnostic control system, interactive control system, belief/boundary system, institutional issues, performance issues, compliance issues